African Ethnobotany in the Americas - Egleé L. Zent (Ethnobiology Letters, 2013)
Review of African Ethnobotany in the Americas. Edited by Robert Voeks and John Rashford. 2013. Springer. Pp. 429, 105 illustrations, 69 color illustrations. $49.95 (paperback). ISBN 978‐1461408352.